Financial Ratios, Firm Size And Board Characteristics' Effect On Indonesia's Consumer Goods Sector Firm Value - Uliansyah, Marji; Kristian Chandra; Farah Margaretha Leon (Ekonomi Digital, 2025)
This study aims to analyze the effect of leverage, profitability, firm size, liquidity, company growth, asset tangibility, board size, and frequency of board meeting on firm value. The dependent variable analyzed is firm value, while the independent variables include leverage, profitability, firm size, liquidity, company growth, asset tangibility, board size, and frequency of board meeting. The research sample focuses on companies in the primary consumer goods sector, specifically in the processed food, beverage, agricultural food products, and personal care product industries listed on the Indonesia Stock Exchange, with 47 companies selected based on specific characteristics relevant and aligned with the research objectives. Data analysis was conducted using multiple regression on panel data processed with data analysis software. The results show that firm value is negatively and significantly effected by firm size and board size. Meanwhile, profitability, liquidity, and asset tangibility have a positive and significant effect. Leverage, company growth, and frequency of board meeting have a positive correlation but do not significantly affect firm value. This study suggests that management should effectively manage profitability, liquidity, and asset tangibility to enhance firm value. Furthermore, investors are advised to prioritize companies with good profitability and liquidity while critically evaluating firm size and board size, which do not always guarantee higher firm value.